CAN ACT IN SUCH CONDITIONS (?): DYNAMICS OF OWNERSHIP OF SPACE FOR HOMELESS IN THE CITY (MONTES CLAROS) - da Luz Alves Ferreira, Maria; Daniele Ramos Tuller, Pâmela (Revista Desenvolvimento Social, 2020)
The work, constructed from participant observation and the free interviews, aimed to reflect on the dynamics of appropriation of spaces for homeless people in the city of Montes Claros/MG, focusing on disputes, convergences and different forms of ownership, in other words, how to act and seek share of social life even in situation of vulnerability and, why not, social oblivion. Initially, a relevant aspect focused on the distribution and diversity of ownership, especially in public spaces. So, the second part of the work (after discussion on the characterization and status of the study population) consisted of about normativity to assert entered the street confronting forms used by the homeless. But the spaces they played seemed to be influenced by interpersonal relationships maintained with work or occupations practiced, but also due to sustained habits, in other wording with the lifestyles developed. Among the places where they lay, some arouse more attention, due to gather larger groups. Those places included in the city center, pool in general to the occupations of respondents. The ultimate goal, therefore, sought to reflect on the particular forms of use of the street as public space and private life: as group, reasons for the choices of local, specific regulations of private spaces (who comes, who goes, what can or not do, what activities are developed), conflicts in relation to external groups authors, different uses over time etc..